ANALISIS KELAYAKAN PENGEMBANGAN USAHA DEPOT AIR MINUM ISI ULANG TIRTA VIT - Arta Rusidarma Putra; Hadi Kurniawanto (Jurnal Bina Bangsa Ekonomika, 2024)
Tirta Vit water depot has plans to develop its business. However, the Tirta Vit Water Depot has problems related to whether the business development plan to be carried out can provide feasibility for future business development. This study aims to determine the business feasibility of drinking water business development plans by using research limitations on assessing market aspects &; financial aspects. Business owners and residents around the place of business are used as objects for interviews and questionnaires. In the market aspect, data analysis is carried out using the Strengths, Weaknesses, Opportunities, Threats (SWOT) Method. Meanwhile, financial aspects are analyzed using the Net Present Value (NPV) Method, Internal Rate of Return (IRR) Method and Payback Period (PBP) Method. The results showed that the Market Aspect of the Tirta Vit Water Depot has Strengths, Weaknesses, Opportunities and Threats that have been analyzed and are in quadrant I (Growth) which means that business conditions are in a state of growth and development. Meanwhile, in terms of Financial Aspects, the results of the Net Present value (NPV) Method show that the NPV calculation results > 0 and positive values with a magnitude reaching Rp. 15,052,070. While the Internal Rate of Return (IRR) shows that 16.671% > the existing interest rate of 12%. and Payback Period Method (PBP) shows that the ability of Tirta Vit water depot to return overall investment costs is 8 months. The conclusion of the results of the financial analysis shows that the overall financial feasibility criteria have been met, so business development is feasible under normal conditions